Study of high indium InXGa1-XN alloys with synchrotron radiation - Wei Zheng; Zhe Chuan Feng; Rui Sheng Zheng; Hao-Hsiung Lin; Xin Qiang Wang; Ting-Shan Chan; Ling-Yun Jang; Chee Wee Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
InGaN thin films with near entire indium composition range have been successfully grown on GaN/sapphire (0001) by molecular beam epitaxy (MBE). X-ray absorption fine structure  have been used to study the local structure of some typical InxGa1-xN alloys with high indium (In) composition of x=0.78 and 0.86. A detailed analysis of the extended x-ray absorption fine structure of In K-edge by using the IFEFFIT program, and the chemical bonds of In-N are obtained. The x-ray absorption near-edge structure of In K- and L-edge and N K-edge are investigated, and the electronic structure of InxGa1-xN are determined with these high In content InxGa1-xN ternary compounds. The calculated XANES spectra of N K-edge, based on first principle method, are consistent with the observed spectra. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2050